Characteristics of spontaneous nystagmus and its correlation to video head impulse test findings in vestibular neuritis - Zhang, Xueqing; Deng, Qiaomei; Liu, Yao; Li, Shanshan; Wen, Chao; Liu, Qiang; Huang, Xiaobang; Wang, Wei; Chen, Taisheng (Frontiers in Neuroscience, 2023)
Objective To explore the direction and SPV (slow phase velocity) of the components of spontaneous nystagmus (SN) in patients with vestibular neuritis (VN) and the correlation between SN components and affected semicircular canals (SCCs). Additionally, we aimed to elucidate the role of directional features of peripheral SN in diagnosing acute vestibular syndrome. Materials and methods A retrospective analysis was conducted on 38 patients diagnosed with VN in our hospital between 2022 and 2023. The direction and SPV of SN components recorded with three-dimensional videonystagmography (3D-VNG) and the video head impulse test (vHIT) gain of each SCC were analyzed as observational indicators. We examined the correlation between superior and inferior vestibular nerve damage and the direction and SPV of SN components, and vHIT gain values in VN patients. Results The median illness duration of between symptom onset and moment of testing was 6 days among the 38 VN patients (17 right VN and 21 left VN). In total, 31 patients had superior vestibular neuritis (SVN), and 7 had total vestibular neuritis (TVN). Among the 38 VN patients, all had horizontal component with an SPV of (7.66 ± 5.37) °/s, 25 (65.8%) had vertical upward component with a SPV of (2.64 ± 1.63) °/s, and 26 (68.4%) had torsional component with a SPV of (4.40 ± 3.12) °/s. The vHIT results in the 38 VN patients showed that the angular vestibulo-ocular reflex (aVOR) gain of the anterior (A), lateral (L), and posterior (P) SCCs on the ipsilesional side were 0.60 ± 0.23, 0.44 ± 0.15 and 0.89 ± 0.19, respectively, while the gains on the opposite side were 0.95 ± 0.14, 0.91 ± 0.08, and 0.96 ± 0.11, respectively. There was a statistically significant difference in the aVOR gain between the A-, L-SCC on the ipsilesional side and the other SCCs (p < 0.001). The aVOR gains of A-, L-, and P-SCC on the ipsilesional sides in 31 SVN patients were 0.62 ± 0.24, 0.45 ± 0.16, and 0.96 ± 0.10, while the aVOR gains on the opposite side were 0.96 ± 0.13, 0.91 ± 0.06, and 0.98 ± 0.11, respectively. There was a statistically significant difference in the aVOR gain between the A-, L-SCC on the ipsilesional side and the other SCCs (p < 0.001). In 7 TVN patients, the aVOR gains of A-, L-, and P-SCC on the ipsilesional side were 0.50 ± 0.14, 0.38 ± 0.06, and 0.53 ± 0.07, while the aVOR gains on the opposite side were 0.93 ± 0.17, 0.90 ± 0.16, and 0.89 ± 0.09, respectively. There was a statistically significant difference in the aVOR gain between the A-, L-, and P-SCC on the ipsilesional side and the other SCCs (p < 0.001). The aVOR gain asymmetry of L-SCCs in 38 VN was 36.3%. The aVOR gain asymmetry between bilateral A-SCCs and bilateral P-SCCs for VN patients with and without a vertical upward component was 12.8% and 8.3%, which was statistically significant (p < 0.05). For VN patients with and without a torsional component, the aVOR gain asymmetry of bilateral vertical SCCs was 17.0% and 6.6%, which was statistically significant (p < 0.01). Further analysis revealed a significant positive correlation between the aVOR gain asymmetry of L-SCCs and the SPV of the horizontal component of SN in all VN patients (r = 0.484, p < 0.01), as well as between the asymmetry of bilateral vertical SCCs and the SPV of torsional component in 26 VN patients (r = 0.445, p < 0.05). However, there was no significant correlation between the aVOR gains asymmetry of bilateral A-SCCs and P-SCCs and the SPV of the vertical component in 25 VN patients. Conclusion There is a correlation between the three-dimensional direction and SPV characteristics of SN and the aVOR gain of vHIT in VN patients. These direction characteristics can help assess different SCCs impairments in patients with unilateral vestibular diseases.